2021
DOI: 10.1039/d1ra03078g
|View full text |Cite
|
Sign up to set email alerts
|

Highly selective fluorescent turn-on–off sensing of OH, Al3+ and Fe3+ ions by tuning ESIPT in metal organic frameworks and mitochondria targeted bio-imaging

Abstract: ESIPT tuned fluorescence sensing of OH−, Al3+ and Fe3+ ions and mitochondria targeted bio-imaging by a Zn-DHNDC MOF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 61 publications
0
10
0
Order By: Relevance
“…To overcome the existing obstacles, introducing the excited-state intramolecular proton transfer (ESIPT) process with huge luminescence Stokes shifts, ultrafast response, and light stability into MOFs may be an effective method to greatly improve the sensitivity and selectivity for water sensing. After being stimulated by light, the ESIPT process can generate rapid intramolecular proton transfer between the hydrogen bond donors (−OH and −NH 2 ) and hydrogen bond acceptors (N– and CO) of the molecular structure via tautomerism from the excited enol form to keto form. Based on this, 2,5-dihydroxyterephthalic acid (DHBDC) was selected to design LMOFs. DHBDC combines the abilities to construct stable MOFs and realize a high-efficiency ESIPT process originating from weak intramolecular H-bonds between two uncoordinated 2,5-hydroxyl groups and the chelate carboxylate oxygen. The added water interacts with the −OH groups of DHBDC and affects the enol–keto tautomerism during the ESIPT process.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome the existing obstacles, introducing the excited-state intramolecular proton transfer (ESIPT) process with huge luminescence Stokes shifts, ultrafast response, and light stability into MOFs may be an effective method to greatly improve the sensitivity and selectivity for water sensing. After being stimulated by light, the ESIPT process can generate rapid intramolecular proton transfer between the hydrogen bond donors (−OH and −NH 2 ) and hydrogen bond acceptors (N– and CO) of the molecular structure via tautomerism from the excited enol form to keto form. Based on this, 2,5-dihydroxyterephthalic acid (DHBDC) was selected to design LMOFs. DHBDC combines the abilities to construct stable MOFs and realize a high-efficiency ESIPT process originating from weak intramolecular H-bonds between two uncoordinated 2,5-hydroxyl groups and the chelate carboxylate oxygen. The added water interacts with the −OH groups of DHBDC and affects the enol–keto tautomerism during the ESIPT process.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Fig. 3, H 2 L has suitable situation among the other chemosensors in terms of low LOD value [12][13][14][15][16][17][18][19][20][21].…”
Section: The Chemical Reversibility Behaviormentioning
confidence: 99%
“…Moreover, luminescent materials with the ability of transferring a hydrogen (H) atom from a donor moiety to an acceptor one upon photoexcitation (a process known as excited-state intramolecular proton transfer, ESIPT) are also excellent candidates for detecting changes in the surrounding environment, , since the modulation of the ESIPT reaction induces changes in the luminescent properties of the material, and their large Stokes shift minimizes or prevents undesired photophysical phenomena such as autoabsorption. , Hence, the combination of MOFs and ESIPT linkers is a great opportunity to develop advanced LMOF materials capable of detecting multiple external stimuli. The ESIPT process in MOFs can occur either as a result of an ESIPT reaction in the organic linkers or in ESIPT molecules encapsulated within the MOF pores . In this sense, one of the most commonly used organic linkers for the fabrication of ESIPT-based LMOFs is 2,5-dihydroxyterephthalic acid (DHT). This linker can emit light from the enol (blue color) or keto (green-yellowish color) tautomers when it is part of the MOF network, and the ultimate emission color of the material depends on the efficiency of the ESIPT reaction to form the keto species. , For example, it has been reported that depending on the metal used in the synthesis, the DHT-based MOFs had different crystalline structures, affecting the ESIPT reaction and, therefore, modifying the final emission color of the material .…”
Section: Introductionmentioning
confidence: 99%